2018
DOI: 10.1182/bloodadvances.2018021063
|View full text |Cite
|
Sign up to set email alerts
|

STAT5 is essential for IL-7–mediated viability, growth, and proliferation of T-cell acute lymphoblastic leukemia cells

Abstract: T-cell acute lymphoblastic leukemia (T-ALL) constitutes an aggressive subset of ALL, the most frequent childhood malignancy. Whereas interleukin-7 (IL-7) is essential for normal T-cell development, it can also accelerate T-ALL development in vivo and leukemia cell survival and proliferation by activating phosphatidylinositol 3-kinase/protein kinase B/mechanistic target of rapamycin signaling. Here, we investigated whether STAT5 could also mediate IL-7 T-ALL-promoting effects. We show that IL-7 induces STAT pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
61
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(70 citation statements)
references
References 99 publications
9
61
0
Order By: Relevance
“…Furthermore, we demonstrate the synergistic potential of combining DEX with these agents and propose that combination therapy may allow for a reduction in DEX dosing, thereby minimizing the numerous acute and chronic toxicities associated with steroid exposure (31) while simultaneously maximizing efficacy. In addition, our data demonstrate that STAT5B was primarily responsible for the upregulation of BCL-2 expression in this context, consistent with previous reports demonstrating that knockdown of STA-T5A is insufficient to modulate IL-7-mediated regulation of BCL-2 expression (11). Interestingly, this is also consistent with the finding that activating mutations in STAT5B, but not STAT5A, commonly occur in T-ALL (1).…”
Section: Methodssupporting
confidence: 92%
See 1 more Smart Citation
“…Furthermore, we demonstrate the synergistic potential of combining DEX with these agents and propose that combination therapy may allow for a reduction in DEX dosing, thereby minimizing the numerous acute and chronic toxicities associated with steroid exposure (31) while simultaneously maximizing efficacy. In addition, our data demonstrate that STAT5B was primarily responsible for the upregulation of BCL-2 expression in this context, consistent with previous reports demonstrating that knockdown of STA-T5A is insufficient to modulate IL-7-mediated regulation of BCL-2 expression (11). Interestingly, this is also consistent with the finding that activating mutations in STAT5B, but not STAT5A, commonly occur in T-ALL (1).…”
Section: Methodssupporting
confidence: 92%
“…One critical endogenous factor in the T-ALL microenvironment is the cytokine IL-7. In addition to promoting the survival and differentiation of developing thymocytes (10), the IL-7 receptor/ JAK/STAT5 (IL-7R/JAK/STAT5) signaling pathway contributes to T-ALL pathogenesis and disease maintenance (11)(12)(13). We previously demonstrated that over half of primary treatment-naive T-ALL patient samples were intrinsically resistant to the glucocorticoid dexamethasone (DEX) when cultured in the presence of IL-7.…”
Section: Glucocorticoids Paradoxically Facilitate Steroid Resistance mentioning
confidence: 99%
“…3e; downregulation as well as Bcl-2 upregulation 73,74 . In agreement, IL-7-mediated Bcl-2 upregulation in T-ALL cells appears to be STAT5-independent 75 -again in opposition to the fact that IL-7mediated STAT5 activation in naïve T-cells associates with survival 71 , suggesting that IL-7-…”
Section: Idiosyncrasies Of Il-7-mediated Signaling In Healthy and Leumentioning
confidence: 77%
“…Previous report suggested that BCR-ABL oncogene mimics pre-BCR signaling by activating STAT5 on one hand and repressing BCL6 expression on the other hand 7 . STAT5 was also shown to directly downregulate BCL6 expression in response to IL7 stimulation 43 . This is in agreement with our data showing that BCR-ABL1 transformation downregulates the transcription repressor BCL6.…”
Section: Discussionmentioning
confidence: 99%